THE EFFECT OF HALAL TOURISM DEVELOPMENT ON THE INCOME OF MSMEs AROUND PADANG BEACH - MAYANG LARASATI (Universitas Islam Negeri Imam Bonjol Padang, 2022)
MSMEs are an important part of the economy. Many efforts have been made by the government to support the performance of MSMEs, one of which is through the tourism object development sector. The existence of a tourist object is expected to be able to encourage MSMEs income in the tourist attraction area. This study uses a quantitative method with the aim of seeing the effect of developing halal tourism objects with location, promotion, accessibility, facilities, and accommodation variables on MSME income around Padang Beach. The research sample is 100 MSMEs around Padang Beach. SPSS version 25 was used to analyze the data in this study. The results of the study show that: 1) location has a positive and significant effect on MSMEs income; 2) tourism promotion has a positive and significant effect on MSMEs income; 3) accessibility has a positive and significant effect on MSMEs income; 4) facilities have a positive but not significant effect on MSMEs income; 5) accommodation has a negative and insignificant effect on MSMEs income; 6) location, tourism promotion, accessibility, facilities, and accommodation all simultaneously have a positive and significant effect on the income of MSMEs around Padang Beach.